Apoptotic responses stimulated by the trichloroethylene metabolite S-(1, 2-dichlorovinyl)-L-cysteine depend on cell differentiation state in BeWo human trophoblast cells. (February 2023) - Su, Anthony L.; Loch-Caruso, Rita
Abstract: During pregnancy, the placental villous cytotrophoblasts differentiate via cell fusion and multinucleation to create syncytiotrophoblasts, a cell type at the maternal-fetal interface. Apoptosis of syncytiotrophoblasts is associated with adverse pregnancy outcomes. The human trophoblast BeWo cell line has been used as an in vitro model for this differentiation process, also known as syncytialization. In the current study, we exposed unsyncytialized BeWo cells, BeWo cells undergoing syncytialization, and syncytialized BeWo cells to S -(1, 2-dichlorovinyl)-L-cysteine (DCVC), a metabolite of the industrial chemical trichloroethylene (TCE). DCVC exposure at 50 μM for 48 h decreased cell viability, increased cytotoxicity, increased caspase 3/7 activity, and increased nuclear condensation or fragmentation in BeWo cells regardless of their differentiation status. Investigating mechanisms of apoptosis, DCVC increased H2 O2 abundance and decreased PRDX2 mRNA in all three BeWo cell models. DCVC decreased tumor necrosis factor-receptor 1 (TNF-R1) concentration in media and decreased NFKB1 and PRDX1 mRNA expression in syncytialized BeWo cells only. DCVC decreased BCL2 mRNA expression in syncytializing BeWo cells and in syncytialized BeWo cells only. Decreased LGALS3 mRNA was seen in unsyncytialized BeWo cells only. Together, these data suggest roles for oxidative stress and pro-inflammatory mechanisms underlying apoptosis in BeWo cells with differences depending on differentiation state. Graphical abstract: Unlabelled Image Highlights: DCVC stimulated apoptosis in three different differentiation states of BeWo cells. Magnitude of apoptosis depended on the differentiation state of the BeWo cells. DCVC decreased PRDX2 and increased H2 O2 abundance in all three BeWo models. DCVC decreased NFKB1 and media TNF-R1 in syncytialized BeWo cells only. DCVC decreased PRDX1 in syncytialized BeWo cells only.